Work environment, workload, perceived organizational support, proactive personality and stress among nurses - Syazwina, lsanuddin (2018)
The main objective of the study is to investigate the impact of work environment, workload, perceived organizational support, and proactive personality on stress among nurses. A total of315 nurses participated in the study. The findings of this study reported that there was a significant and positive relationship between work environment and stress. However, the relationship between other independent variables and stress was not substantiated. Discussions explained the research findings. Besides that, this study also presents the theoretical and practical implications, research limitations, directions for future research, and conclusion.